PERBEDAAN TINGKAT AKURASI SKALA FACE ARM SPEECH TEST SKALA LOS ANGELES PREHOSPITAL STROKE SCREEN DAN SKALA RECOGNITION OF STROKE IN THE EMERGENCY ROOM DALAM MENGIDENTIFIKASI PASIEN STROKE - Suska Lara Ginting,* Rusli Dhanu,* Fasihah Irfani Fitri* (NEURONA, 2017)
INTRODUCTION ACCURATE IDENTIFICATION OF STROKE IS IMPORTANT FOR DELIVERING ACUTE STROKE THERAPIES IN HOSPITAL THE FACE ARM SPEECH TEST FAST IS A BRIEF RELIABLE TOOL THAT IS SIMPLE TO ADMINISTER FOR STROKE PATIENT IDENTIFICATION THE RECOGNITION OF STROKE IN EMERGENCY ROOM ROSIER IS NOT BETTER THAN THE FAST FOR RECOGNITION OF STROKE THE PARAMEDICS OF BEIJING USE LOS ANGELES PREHOSPITAL STROKE SCALE LAPSS AS A SCREENING TOOL TO IDENTIFY STROKE AND ALSO TO EXCLUDE STROKE MIMICS